Teacher Self-Efficacy as the Key to Success Inclusive Education: Case Study at Madrasahs in Banten - Abdurrahman Taufik, Opik; Lisyawati, Elis; Aznan Che Ahmad (Mozaic : Islam Nusantara, 2025)
Inclusive education aims to provide equal learning opportunities for all students, including those with special needs, by fostering collaboration and diversity within classroom environments. However, its successful implementation in Indonesia’s madrasahs remains a challenge, particularly due to limited teacher readiness and lack of special education expertise. This study explores the role of teacher self-efficacy as a key factor in the success of inclusive education in four madrasahs in Banten Province. Using a qualitative approach, data was collected through in-depth interviews, participatory observation, and documentation analysis. Thematic analysis and triangulation methods were applied to ensure data validity and reliability. The findings reveal that teachers’ self-efficacy strongly influences their motivation, classroom management, and responsiveness to the diverse needs of students with disabilities. Most assistant teachers lack formal training in special education and rely on self-directed learning or informal peer support, leading to varied implementation quality. Teachers with high self-efficacy demonstrate greater perseverance, creativity, and emotional resilience, while those with low self-efficacy tend to experience anxiety and reduced teaching effectiveness. The study highlights the importance of distributed leadership, continuous professional development, and institutional support in strengthening teacher self-efficacy. It concludes that enhancing self-efficacy among madrasah teachers is essential to sustaining inclusive education that aligns with both pedagogical goals and Islamic values of compassion and equality.